Imrecoxib attenuates osteoarthritis by modulating synovial macrophage polarization through inactivating COX-2/PGE2 signaling pathway - Peng, Peng; Zheng, Wanling; Liu, Yuchen; Huang, Jingyuan; Zhang, Bin; Shen, Jiawei; Cao, Jiangang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAlthough biomaterials strategies have been regarded as a promising approach for the treatment of osteoarthritis (OA), identifying novel drugs to be delivered for modulate macrophage polarization is still unclear. As a commonly used non-steroidal anti-inflammatory drug for OA, Imrecoxib may be a novel drug to direct and sustain macrophage phenotype. However, the specific protective mechanism of Imrecoxib in OA remains unclear. This study aims to investigate whether Imrecoxib would treat OA by regulating synovial macrophage polarization.MethodsThe research involves constructing mouse destabilization of medial meniscus (DMM) model to assess the changes in pain, bone destruction, cartilage degeneration, and synovial macrophage phenotypes following Imrecoxib treatment. Additionally, the effects of macrophage conditioned medium (CM) pretreated with Imrecoxib on the chondrocyte apoptosis, inflammation and degeneration-related factor expression were evaluated. The role of COX-2/PGE2 signaling pathway in the macrophage phenotype changes was further investigated.ResultsWe found that Imrecoxib alleviated pain, cartilage degeneration and synovitis, promoted polarization of M1 macrophages toward M2 phenotype in vivo and in vitro. In vitro experiments, Imrecoxib-CM protected chondrocyte by modulating macrophage polarization. Furthermore, Imrecoxib regulates macrophage polarization through the COX-2/PGE2 pathway.ConclusionThis study unravels that Imrecoxib protects joint cartilage and attenuates osteoarthritis by modulating synovial macrophage polarization through inactivating COX-2/PGE2 signaling pathway, providing new drug delivery strategy for the clinical treatment of OA.